The MAP Kinase CfPMK1 Is a Key Regulator of Pathogenesis, Development, and Stress Tolerance of Colletotrichum fructicola - Liang, Xiaofei; Wei, Tingyu; Cao, Mengyu; Zhang, Xin; Liu, Wenkui; Kong, Yuanyuan; Zhang, Rong; Sun, Guangyu (Frontiers in Microbiology, 2019)
The Ascomycetes fungus Colletotrichum fructicola causes severe diseases on a wide range of crops, fruits, and vegetables. Its pathogenic mechanisms, however, remain poorly understood. Mitogen-activated protein kinases (MAPKs) are conserved regulators of fungal development and pathogenesis. In this study, a Fus3/Kss1-related MAPK from C. fructicola was functionally characterized via gene deletion. On potato dextrose agar (PDA) and oatmeal agar media, the CfPMK1 gene deletion mutants (ΔCfPMK1) were slightly reduced in radial growth rate, severely limited in aerial hyphal differentiation and hyphal melanization, and formed deformed perithecia that were smaller in size and more compactly organized relative to wild type. When artificially inoculated on plants, conidia of these mutants failed to differentiate appressoria or penetrate cuticle, and their pathogenicity defect could not be rescued by wounding plant tissue prior to inoculation. On PDA, ΔCfPMK1 mutants were hypersensitive to osmotic stresses, but were more tolerant to membrane and cell wall stresses. Genetic complementation rescued all phenotypic changes associated with CfPMK1 gene deletion. Based on GFP fusion expression, CfPMK1 protein accumulation was detected at all life stages, and the accumulation level was higher in nascent appressoria relative to conidia. Overall, this study identified CfPMK1 as a key regulator of appressorium and sexual development, pathogenesis, and stress tolerance in C. fructicola.